Preparation and characterisation of lithium ion exchange composite for the recovery of lithium from brine. Issue 3 (3rd July 2018) - Zandvakili, Saeid; Ranjbar, Mohammad
ABSTRACT: This paper presents the characterisation and application of a new ion exchange composite, manufactured by poly vinylidene fluoride (PVDF) for recovery of lithium from natural brine. Synthesised MnO2 nano particles (HMO, final MnO2 ion-sieve) having high selectivity for lithium adsorption were used as inorganic ion-exchange adsorbent. Subsequently, the lithium ion exchange composite (CHMO, final MnO2 ion exchange composite) was prepared by dissolving PVDF in N -methyl-2-pyrrolidone, and mixing with (HMO) in equal ratios. The produced polymeric solution acts as a binder and support to closely bond HMO together into a homogeneous three-dimensionally interpenetrating network after drying at 220°C. This composite presents a mesoporous/macroporous structure which allows free channel of the solution. It exhibits considerable Li + adsorption capacities of 19.22 and 11.06 mg(Li + ) g −1 (CHMO) in LiOH solution and lithium-enriched Lake Urmia, respectively. Efforts for improvement of the overall performances of CHMO are still in progress.